Implementation and evaluation of treatments for children and adolescents with conduct problems: Findings, challenges, and future directions - Kazdin, Alan E. (Psychotherapy research, 2018)
Objective: The intervention work of our clinical-research team has focused on the treatment of children and young adolescents referred for Conduct Disorder or Oppositional Defiant Disorder. Method: We have evaluated two interventions: parent management training (PMT) and cognitive problem-solving skills training in several randomized controlled clinical trials. Results: Our findings have indicated the treatments, alone or in combination, produce reliable and significant reductions in oppositional, aggressive, and antisocial behaviour and increases in prosocial behaviour among children. Parent dysfunction (depression, multiple symptom domains) and stress decline and family relations improve as well. Apart from outcome studies, we have studied the therapeutic alliance, factors that influence dropping out and retaining cases, and variations of treatment delivery (e.g., computer based, reduced therapist contact). Conclusions: The article considers challenges in conducting controlled trials in clinic settings (e.g., recruiting cases, maintaining treatment integrity, securing funding) and activities related to implementation that are not easily covered within the confines of research articles. The article ends with a discussion of one of the treatments (PMT) and the broad role it can play in treatment, prevention, and help with many parenting challenges of everyday life.